Learning Ensembles of First Order Clauses That Optimize Precision Recall Curves - Goadrich, Mark H. (University of Wisconsin-Madison Department of Computer Sciences, 2007)
Many domains in the field of Inductive Logic Programming (ILP) involve highly unbalanced data, such as biomedical information extraction, citation matching, and learning relationships in social networks. A common way to measure performance in these domains is to use precision and recall instead of simply using accuracy, and to examine their trade-offs by plotting a precision-recall curve. The goal of this thesis is to find new approaches within ILP particularly suited for large, highly skewed domains. I propose and investigate Gleaner, a randomized search method that collects good clauses from a broad spectrum of points along the recall dimension in recall-precision curves and employs thresholding methods to combine sets of selected clauses. I compare Gleaner to ensembles of standard theories learned by Aleph, a standard ILP algorithm, using a number of large relational domains. I find that Gleaner produces comparable testset results in a fraction of the training time and outperforms Aleph ensembles when given the same amount of training time. I explore extensions to Gleaner with respect to searching and combining clauses, namely finding ways to fully explore the hypothesis space as well as to make better use of those found clauses. I also use Gleaner to estimate the probability that a query is true, further investigate the properties underlying precision-recall curves, and then conclude with a discussion of future work in this area.